Gold Nanoparticles Dissolve Extracellularly in the Presence of Human Macrophages - McCarrick, Sarah; Midander, Klara; Krausová, Magdaléna; Carlander, Ulrika; Karlsson, Hanna L (International journal of nanomedicine, 2021)
Gold nanoparticles (AuNPs) have the potential to be used in various biomedical applications, partly due to the inertness and stability of gold. Upon intravenous injection, the NPs interact with the mononuclear phagocyte system, first with monocytes in the blood and then with macrophages in tissue. The NP-macrophage interaction will likely affect the stability of the AuNPs, but this is seldom analyzed. This study aimed to elucidate the role of macrophages in the biodissolution of AuNPs and underlying mechanisms. With an in vitro dissolution assay, we used inductively coupled plasma mass spectrometry to quantitatively compare the dissolution of 5 and 20 nm AuNPs coated with citrate or PEG in cell medium alone or in the presence of THP1-derived macrophages at 24 hours. In addition, we analyzed the cell dose, compared extra- and intracellular dissolution, and explored the possible role of reactive nitrogen species. The results showed a higher cellular dose of the citrate-coated AuNPs, but dissolution was mainly evident for those sized 5 nm, irrespective of coating. The macrophages clearly assisted the dissolution, which was approximately fivefold higher in the presence of macrophages. The dissolution, however, appeared to take place mainly extracellularly. Acellular experiments demonstrated that peroxynitrite can initiate oxidation of gold, but a ligand is required to keep the gold ions in solution. This study suggests extracellular dissolution of AuNPs in the presence of macrophages, likely with the contribution of the release of reactive nitrogen species, and provides new insight into the fate of AuNPs in the body.